The Wnt/β-catenin signaling pathway in colorectal cancer: mechanism and intervention of traditional Chinese medicine and chemical compound - Zeng, Sha; Wang, Juan; Shi, Zhengrong; Zhao, Hui; Gao, Jingxing; Li, Jinxiu (Frontiers in Pharmacology, 2025)
Colorectal cancer (CRC) is globally recognized as the third most frequently diagnosed malignancy and the second leading cause of cancer-related mortality. The etiology of CRC is multifactorial, arising from a complex interplay of genetic alterations, environmental exposures, and age-related physiological changes. Among the numerous signaling pathways that regulate cellular homeostasis, the Wnt/β-catenin signaling pathway not only plays a critical role in embryonic development and cell proliferation but also contributes to the initiation and progression of various malignancies, including CRC. Dysregulation of the Wnt/β-catenin signaling pathway is a hallmark of CRC, playing a pivotal role in regulating chemoresistance and driving invasive and metastatic behaviors. Traditional Chinese Medicine (TCM) is characterized by its multi-target and multi-pathway mechanisms. Extensive studies have demonstrated that TCM can inhibit the activity of CRC cells by targeting the Wnt/β-catenin signaling pathway and significantly alleviate symptoms in CRC animal models, demonstrating its potential therapeutic value for the treatment of CRC. This review primarily focuses on the literature published in the past 5 years, retrieved from databases such as PubMed, Web of Science, Scopus, MEDLINE, and Springer, concerning the targeting of the Wnt/β-catenin signaling pathway for the treatment of CRC. It highlights the research progress on TCM monomers (e.g., myricetin, genistein, baicalein), TCM formulations (e.g., Pai-Nong-San (PNS), Jian-Du-Xiao-Sheng Yin (JXY), Zuo-Jin-Wan (ZJW)), and small-molecule inhibitors (e.g., PCDHGA9, Cetuximab, PTK7). Furthermore, the experimental results and conclusions from these studies are thoroughly analyzed and discussed. Through a comprehensive review of the literature, we conclude that TCM exhibits multi-level, multi-target, and multi-faceted effects in the prevention and treatment of CRC. In-depth research into the mechanisms by which TCM targets the Wnt/β-catenin signaling pathway to prevent and treat CRC may provide novel insights into exploring the pathogenesis of CRC and developing new therapeutic agents for CRC.